Youth perceptions of agriculture: influence of cognitive processes on participation in agripreneurship. Issue 2 (17th February 2020) - Magagula, Buyisile; Tsvakirai, Chiedza Z.
ABSTRACT: This article investigates the nature of youth perceptions and their influence on youth's intentions of engaging in agripreneurship. The study findings reveal that the youth held positive economic perceptions of the agricultural sector. Along with the provision of secondary school agricultural education and a significant amount of financial support, these perceptions positively influenced their intentions to participate in agripreneurship. The findings affirm the need for improving awareness of the economic opportunities available in the agricultural sector. The study recommends that programmes that aim to encourage agripreneurship target both the socio-economic and cognitive limitations of youths.